MAHASISWA ORGANISATORIS UBSI BOGOR MEMBERIKAN PENGAJARAN SUKARELA DI KAMPUNG MONGOL BOGOR - Putra, Octa Pratama; Pravitha, Cattleya Wahyu (Politeknik Perkeretaapian Indonesia Madiun, 2025)
The purpose of this community service activity is to improve access to education through the implementation of a voluntary teaching program located in Kampung Mongol, Bogor, West Java. This activity involves 13 (thirteen) organizational and legal students and 3 (three) volunteer students. The program, called BEM Mengajar (Student Executive Board Teaching), is designed to provide an interactive and enjoyable learning experience. This study uses a qualitative method with data collection techniques including observation, interviews, and documentation. The learning process was carried out four times every Saturday, from 10:00 to 11:30 AM, during July 2024 (on the 6th, 13th, 20th, and 27th). The topics being teaching are: Basic English, Basic Science, Basic Social Studies, and Basic Indonesian. The learning approach used emphasizes acronym strategies as a method to enhance students' understanding. The results of the activity show that the use of acronym strategies is able to create a fun, interactive learning atmosphere and facilitates understanding of the material. This is evidenced by participation data, attendance rates, participant responses, as well as observation and interview results during the activity. The learning process not only focuses on text-based material delivery but is packaged through creative activities that optimize the right brain, such as illustrations, imagination, and fun activities relevant to the participants' daily lives.